2020
DOI: 10.1038/s42004-020-00357-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the formation of dimers of polycyclic aromatic hydrocarbons in a laminar diffusion flame

Abstract: The role of polycyclic aromatic hydrocarbons (PAHs) in the formation of nascent soot particles in flames is well established and yet the detailed mechanisms are still not fully understood. Here we provide experimental evidence of the occurrence of dimerization of PAHs in the gas phase before soot formation in a laminar diffusion methane flame, supporting the hypothesis of stabilization of dimers through the formation of covalent bonds. The main findings of this work derive from the comparative chemical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Although the mechanism of formation of nascent soot particles from PAHs precursors is still discussed in the community, a large number of studies [43,47,[64][65][66][67][68][69] mentioned that moderate sized PAHs as pyrene could play an important role in the nucleation process. More specifically, the formation of dimers of such PAHs has been suggested as a potential key step allowing the formation of nascent soot particles [47,[66][67][68][69][70][71][72][73]. However, because of the weak energy of the Van der Waals bonds characterizing dimers of PAHs, especially at flame temperature [74,75], this hypothesis has often been considered as a numerical tool for kinetic modelling rather than a real physical process actually involved in sooting flames.…”
Section: Impact Of Hydrogen On the Appearance Of Nascent Soot Particlesmentioning
confidence: 99%
“…Although the mechanism of formation of nascent soot particles from PAHs precursors is still discussed in the community, a large number of studies [43,47,[64][65][66][67][68][69] mentioned that moderate sized PAHs as pyrene could play an important role in the nucleation process. More specifically, the formation of dimers of such PAHs has been suggested as a potential key step allowing the formation of nascent soot particles [47,[66][67][68][69][70][71][72][73]. However, because of the weak energy of the Van der Waals bonds characterizing dimers of PAHs, especially at flame temperature [74,75], this hypothesis has often been considered as a numerical tool for kinetic modelling rather than a real physical process actually involved in sooting flames.…”
Section: Impact Of Hydrogen On the Appearance Of Nascent Soot Particlesmentioning
confidence: 99%
“…Tielens et al [19] and Mao et al [20] concluded that weak intermolecular interactions and van der Waals forces are responsible for bond formation arising from the majority of binary collisions between PAH radicals. However, experimental investigations can lead to a contrary conclusion for different flame conditions [21,22]. Furthermore, numerous theoretical studies suggest that closed-shell PAH dimers have very short lifetimes under flame conditions except for species much larger than normally observed in flames [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 98%
“…Polycyclic aromatic hydrocarbons (PAHs) are early intermediates in the soot formation process in both terrestrial [1][2][3] and interstellar environments [4][5][6][7] . Soot and PAHs formed during the incomplete combustion of fossil fuels are detrimental to human health due to their toxic and carcinogenic properties [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%